Addressing the existential dimension in treatment settings: Mental health professionals' and healthcare chaplains' attitudes, practices, understanding and perceptions of value. (November 2019) - Frøkedal, Hilde; Sørensen, Torgeir; Ruud, Torleif; DeMarinis, Valerie; Stifoss-Hanssen, Hans
Research has shown that addressing and integrating the existential dimension in treatment settings reduce symptoms like anxiety, depression and substance abuse. Healthcare chaplains are key personnel in this practice. A nationwide, cross-sectional survey influenced by a mixed-methods approach was used to examine the attitudes, practices, understanding and perceptions of mental health professionals, including healthcare chaplains, regarding the value of addressing the existential dimension in treatment programmes. The existential group practice was led by the healthcare chaplains as an integrated part of specialist mental health services. A positive and open attitude towards addressing the existential dimension was identified among the informants. Despite this, a small gap between attitude and practice was reported. Existential, religious and spiritual concerns are reported as part of the existential dimension and as relevant topics to be discussed in specialist mental health services. The findings indicate that the existential group practice could have a positive influence on the co-leaders' competence to address existential, religious and spiritual concerns; however, this should be further investigated.